Bis(pertrifluoromethylcatecholato)silane: Extreme Lewis Acidity Broadens the Catalytic Portfolio of Silicon. Issue 40 (21st May 2021) - Thorwart, Thaddäus; Roth, Daniel; Greb, Lutz
Abstract: Given its earth abundance, silicon is ideal for constructing Lewis acids of use in catalysis or materials science. Neutral silanes were limited to moderate Lewis acidity, until halogenated catecholato ligands provoked a significant boost. However, catalytic applications of bis(perhalocatecholato)silanes were suffering from very poor solubility and unknown deactivation pathways. In this work, the novel per(trifluoromethyl)catechol, H2 cat CF3, and adducts of its silicon complex Si(cat CF3 )2 (1 ) are described. According to the computed fluoride ion affinity, 1 ranks among the strongest neutral Lewis acids currently accessible in the condensed phase. The improved robustness and affinity of 1 enable deoxygenations of aldehydes, ketones, amides, or phosphine oxides, and a carbonyl‐olefin metathesis. All those transformations have never been catalyzed by a neutral silane. Attempts to obtain donor‐free 1 attest to the extreme Lewis acidity by stabilizing adducts with even the weakest donors, such as benzophenone or hexaethyl disiloxane. Abstract : The extremely electron‐deficient tetratrifluorocatechol is synthesized and installed at silicon, providing a Lewis superacid that ranks among the strongest fluoride ion acceptors accessible in the condensed phase. The compound enables silicon‐catalyzed deoxygenation of ketones, aldehydes, amides and phosphine oxides and the first silicon catalyzed carbonyl‐olefin metathesis.